2013
DOI: 10.1038/srep01535
|View full text |Cite
|
Sign up to set email alerts
|

A library of programmable DNAzymes that operate in a cellular environment

Abstract: DNAzymes were used as inhibitory agents in a variety of experimental disease settings, such as cancer, viral infections and even HIV. Drugs that become active only upon the presence of preprogrammed abnormal environmental conditions may enable selective molecular therapy by targeting abnormal cells without injuring normal cells. Here we show a novel programmable DNAzyme library composed of variety of Boolean logic gates, including YES, AND, NOT, OR, NAND, ANDNOT, XOR, NOR and 3-input-AND gate, that uses both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
(34 reference statements)
0
41
0
Order By: Relevance
“…In contrast, many existing methods utilize peroxidase-mimicking DNAzymes (Elbaz et al, 2009;Guo et al, 2010;Qiu et al, 2010;Zhu et al, 2011) which have not yet been demonstrated to catalyze modification of nucleic acid substrates. Additionally, other methods outlined to date may block nucleic acid-modifying DNAzymes with complementary oligonucleotides, however the DNAzyme is typically released the via a strand-displacing mechanism whereby the target simply hybridizes to the complementary (blocking) strand and does not cleave it (Deborggraeve et al, 2013;Kahan-Hanum et al, 2013;Orbach et al, 2012;Tian and Mao 2005;Wang et al, 2002). The two DNAzyme switches outlined here proved to be successful provided an optimal T m existed between the two oligonucleotides for the reaction temperature.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, many existing methods utilize peroxidase-mimicking DNAzymes (Elbaz et al, 2009;Guo et al, 2010;Qiu et al, 2010;Zhu et al, 2011) which have not yet been demonstrated to catalyze modification of nucleic acid substrates. Additionally, other methods outlined to date may block nucleic acid-modifying DNAzymes with complementary oligonucleotides, however the DNAzyme is typically released the via a strand-displacing mechanism whereby the target simply hybridizes to the complementary (blocking) strand and does not cleave it (Deborggraeve et al, 2013;Kahan-Hanum et al, 2013;Orbach et al, 2012;Tian and Mao 2005;Wang et al, 2002). The two DNAzyme switches outlined here proved to be successful provided an optimal T m existed between the two oligonucleotides for the reaction temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Molecular computing elements hold great interest due to their potential to be exploited for logical control of biological processes (Orbach et al, 2012). Such systems may be used to function as "programmable drugs", responding only in the presence of abnormal conditions (Elbaz et al, 2010a;Kahan-Hanum et al, 2013;. To demonstrate potential for computation, we modified a quasi-circular DNAzyme switch (corresponding to Design 2, Fig.…”
Section: Dnazyme Switches For Molecular Computational Logicmentioning
confidence: 99%
“…Previous work applying molecular logic, including DNAzymes, to the problem of classifying and eliminating cancer cells [35,42,43] highlights the potential impact of the DNAzyme-based approach. It is likely that the application of simple machine learning techniques will enable significant advances in these fields by allowing devices to learn appropriate responses to their surroundings rather than relying on a fixed, pre-programmed pattern of behaviour.…”
Section: Related Workmentioning
confidence: 99%
“…Future work will explore the operation of DNAzyme cascades in physiologically relevant conditions [25] such as cell lysate [26] or serum, which may be challenging due to the presence of nucleases that may degrade circuit components, or due to insufficient concentrations of the metal ion cofactors required for efficient DNAzyme catalysis. [27] Furthermore, the modular design of the SCS should allow the implementation of increasingly complex synthetic DNAzyme signaling networks, incorporating network motifs such as feedforward and feedback cycles.…”
mentioning
confidence: 99%